Pengenalan dan Pelafalan Huruf Hijaiyah Siswa Kelas 1B MIT Ar-Rifqi Menggunakan Metode Tilawati - Vina Latifah; Dhany Muharom Albandaniji; izzuddin musthafa; lina marlina (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to describe and analyze the recognition and pronunciation of hijaiyah letters among Class 1B students at Ar-Rifqi Integrated Islamic Elementary School using the Tilawati method, as well as to identify the supporting and inhibiting factors that influence the success of Qur’anic learning through the Tilawati method. This research employed a descriptive qualitative approach. Data were obtained from primary sources, namely teachers and students, and secondary sources in the form of learning documents. Data collection was conducted through observation, interviews, and documentation. Data analysis used an interactive model consisting of data reduction, data presentation, and conclusion drawing. Data validity was maintained through source triangulation to ensure valid and credible findings. The results showed that the implementation of the Tilawati method in Class 1B of MIT Ar-Rifqi was carried out through systematic lesson planning, the use of the Rost melody, the application of classical and individual techniques, and the utilization of learning media that supported the learning process. The implementation of this method demonstrated improvements in students’ ability to recognize the shapes of hijaiyah letters, distinguish letters with similar forms and sounds, and pronounce letters according to their correct makharijul huruf more accurately and fluently. The success of the learning process was supported by teacher competence, the use of engaging learning media, parental support, and regular reading practice. Meanwhile, the inhibiting factors included differences in students’ abilities, the low learning concentration of some students, and limited instructional time.